A systematic assessment of the current capacity to act in nutrition in West Africa: cross-country similarities and differences - FANOU-FOGNY KLOUBOU, NADIA (My University, 2014)
Background: Although it is widely accepted that lack of capacity is one of the barriers to scaling up nutrition in West Africa, there is a paucity of information about what capacities exist and the capacities that need to be developed to accelerate progress toward improved nutrition outcomes in the region. Objective: To systematically assess the current capacity to act in nutrition in the West Africa region and explore cross-country similarities and differences. Design: Data were collected from 13West African countries through interviews with government officials, key development partners, tertiary-level training institutions, and health professional schools. The assessment was based on a conceptual framework of four interdependent levels (tools; skills; staff and infrastructure; and structures, systems and roles). In each of the surveyed countries, we assessed capacity assets and gaps at individual, organizational, and systemic levels. Results: Important similarities and differences in capacity assets and gaps emerged across all the surveyed countries. There was strong momentum to improve nutrition in nearly all the surveyed countries. Most of the countries had a set of policies on nutrition in place and had set up multisectoral, multi-stakeholder platforms to coordinate nutrition activities, although much remained to be done to improve the effectiveness of these platforms. Many initiatives aimed to reduce undernutrition were ongoing in the region, but there did not seem to be clear coordination between them. Insufficient financial resources to implement nutrition activities were a major problem in all countries. The bulk of financial allocations for nutrition was provided by development partners, even though some countries, such as Niger, Nigeria, and Senegal, had a national budget line for nutrition. Sporadic stock-outs of nutrition supplies were reported in most of the countries as a result of a weak logistic and supply chain system. They also had a critical shortage of skilled nutrition professionals. There was limited supervision of nutrition activities, especially at lower levels. Nigeria and Ghana emerged as the countries with the greatest capacities to support the expansion of a nutrition workforce, although a significant proportion of their trained nutritionists were not employed in the nutrition sector. None of the countries had in place a unified nutrition information system that could guide decision-making processes across the different sectors. Conclusions: There is an urgent need for a shift toward wider reforms for nutrition capacity development in the West Africa region. Addressing these unmet needs is a critical first step toward improved capacity for action in nutrition in the region.
Keywords: capacity development; nutrition; undernutrition; nutrition workforce; West Africa